Hereditary spastic paraplegia with recessive trait caused by mutation in KLC4 gene - Bayrakli, Fatih; Poyrazoglu, Hatice Gamze; Yuksel, Sirin; Yakicier, Cengiz; Erguner, Bekir; Sagiroglu, Mahmut Samil; Ziyal, Ibrahim (Nature Publishing Group, 2015)
We report an association between a new causative gene and spastic paraplegia, which is a genetically heterogeneous disorder. Clinical phenotyping of one consanguineous family followed by combined homozygosity mapping and whole-exome sequencing analysis. Three patients from the same family shared common features of progressive complicated spastic paraplegia. They shared a single homozygous stretch area on chromosome 6. Whole-exome sequencing revealed a homozygous mutation (c.853_871del19) in the gene coding the kinesin light chain 4 protein (KLC4). Meanwhile, the unaffected parents and two siblings were heterozygous and one sibling was homozygous wild type. The 19 bp deletion in exon 6 generates a stop codon and thus a truncated messenger RNA and protein. The association of a KLC4 mutation with spastic paraplegia identifies a new locus for the disease.
Keywords: Sequencing Data; Drosophila